Catalyst for preparing aniline through liquid-phase hydrogenation of nitrobenzene as well as preparation method and application of catalyst
By introducing Cu-doped molecular sieve on the ZrO2 fine particles, the ZrO2@Cu-containing framework molecular sieve catalyst with a core-shell structure is formed, and the problem of low conversion efficiency of existing catalysts at low reaction temperature and normal pressure is solved, and aniline preparation is achieved efficient and selective.
Patent Information
- Application Number
- CN202311365408.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-20
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2043-10-20
AI Technical Summary
The existing catalysts for preparing aniline by liquid hydrogenation of nitrobenzene have high cost, high reaction pressure, poor toxicity and cumbersome production steps, making it difficult to achieve efficient conversion at lower reaction temperatures and normal pressures.
Ultrafine ZrO2 is used as the crystal core, and Cu atom-doped molecular sieve is introduced on its surface by hydrothermal crystallization to form a core-shell structure of ZrO2@Cu-containing backbone molecular sieve catalyst to ensure the uniform dispersion and stability of the active component Cu.
It is achieved efficient conversion of nitrobenzene to aniline at lower reaction temperature and normal pressure. The catalyst shows excellent activity, selectivity and stability, with aniline conversion rate reaching 100% and a selectivity reaching 99.99%.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalysts, and specifically relates to a catalyst for preparing aniline by liquid-phase hydrogenation of nitrobenzene, and a preparation method and application thereof. Background Art
[0002] Aniline (English name Aniline, molecular formula C6H7N) is characterized by a colorless, slightly yellow oily liquid. When aniline is exposed to air or sunlight, it appears brown. It has a strong odor. Aniline is slightly soluble in water, but it is miscible with organic solvents such as ethanol, ether and benzene. Aniline is alkaline and can react with hydrochloric acid and sulfuric acid to form hydrochloride and sulfate. It can also undergo reduction, oxidation, halogenation and other reactions. Aniline is one of the most important amine substances and an important organic chemical raw material intermediate. It is mainly used in the production of polyurethane raw material diphenylmethane diisocyanate (MDI), and in the chemical industry fields such as dyes, pesticides, medicines, special fibers, rubber additives and organic intermediates.
[0003] The industrial production methods of aniline include: nitrobenzene iron powder reduction method, phenol direct amination method and nitrobenzene catalytic hydrogenation method. The nitrobenzene iron powder reduction method and the phenol direct amination method have the disadvantages of high preparation cost and not conforming to green production. At present, the mainstream method of aniline production is nitrobenzene catalytic hydrogenation method. Nitrobenzene catalytic hydrogenation method is divided into liquid phase hydrogenation and gas phase hydrogenation. Nitrobenzene catalytic hydrogenation method is divided into fixed bed gas phase catalytic hydrogenation, fluidized bed gas phase catalytic hydrogenation and slurry bed liquid phase catalyst hydrogenation. Gas phase hydrogenation reaction usually requires high reaction temperature and hydrogen pressure, high equipment requirements, high energy consumption and dangerous operation. Liquid phase hydrogenation has the advantages of low reaction temperature, few side reactions, high catalytic load, large equipment production capacity and low total investment, and has gradually become a research hotspot.
[0004] Catalysts for preparing aniline by liquid phase hydrogenation of nitrobenzene are mainly precious metal catalysts in which precious metals such as Pt, Pd and Rh are loaded on carriers such as alumina and activated carbon, such as patent CN103316676A, which loads active component Pt and one of the additives La, Co, Cu and Cr on an alumina carrier by a step-by-step impregnation method; and supported nickel, copper, nano and non-static alloy catalysts, such as patent CN10259414A, which discloses a new method for preparing nano catalysts, using a carrier loaded with an inducer as a precursor, inducing hydrazine hydrate to reduce a nickel salt solution, and forming a directional deposition of nano nickel grains on the surface of the carrier.
[0005] However, these catalysts have many problems such as high price, high reaction pressure, poor toxicity resistance, and complicated production steps. Therefore, the market is in urgent need of a catalyst with high catalytic activity and good selectivity that can convert nitrobenzene into aniline at a relatively low reaction temperature and normal pressure, while also taking into account production costs and being easy to promote industrial production. Summary of the invention
[0006] The purpose of the present invention is to provide a catalyst for preparing aniline by liquid phase hydrogenation of nitrobenzene and a preparation method and application thereof.
[0007] The main feature of the present invention is that ultrafine ZrO2 is used as a crystal nucleus, and a Cu atom-doped molecular sieve is introduced on its surface in the form of hydrothermal crystallization to form a ZrO2@Cu-containing skeleton molecular sieve with a core-shell structure. Cu, as an active component, is dispersed in the molecular sieve skeleton in the form of embedding, and anchors the active component Cu to avoid its migration during use and the consequence of copper grain growth. ZrO2 is used as a carrier matrix to make the carrier structure stable and the pore structure suitable, which is beneficial to improving the shape selectivity of the product and promoting the heat dissipation of the reaction, thereby improving the activity, selectivity and stability of the catalyst.
[0008] To achieve the above object, the present invention proposes the following technical solutions: In the first aspect, the present invention discloses a catalyst for preparing aniline by liquid phase hydrogenation of nitrobenzene, wherein the catalyst has a core-shell structure of ZrO2@Cu-containing skeleton molecular sieve, wherein the molecular sieve structure is a modified molecular sieve doped with active component Cu, and the carrier content is 70-80% by mass percentage, the ZrO2 / molecular sieve mass ratio is 1:1-1:4, and the active component CuO content is 20-30%. The specific surface area of the catalyst of the present invention is 180-350 2 / g, average pore diameter 15-35nm, pore volume 0.21-0.45cm3 / g.
[0009] In a second aspect, the present invention discloses a method for preparing a catalyst for preparing aniline by liquid phase hydrogenation of nitrobenzene, comprising the following steps: 1) adding zirconium salt into alkaline solution under the action of ultrasound to prepare a suspension of ultrafine nanocrystalline cores; 2) After uniformly mixing silica sol, inorganic aluminum salt, alkaline solution and organic ammonium template, Cu salt is added under ultrasonic action to obtain gel; wherein the inorganic aluminum salt is one of aluminum sulfate, aluminum nitrate, aluminum chloride and aluminum hydroxide; 3) adding the gel in step 2) to the suspension in step 1) and continuing stirring for 20-40 minutes to obtain a catalyst precursor solution; 4) Under temperature control conditions, the catalyst precursor solution is subjected to hydrothermal crystallization treatment in a reactor; 5) The product of the hydrothermal crystallization treatment is washed, filtered, dried, granulated, calcined and formed to obtain a core-shell structure ZrO2@Cu-containing skeleton molecular sieve catalyst.
[0010] Furthermore, the alkali in the alkali solution in steps 1) and 2) is NaOH or KOH.
[0011] Furthermore, the organic ammonium template in step 2) is tetrabutylammonium bromide, tetrapropylammonium bromide, tetrabutylammonium hydroxide or tetrapropylammonium hydroxide.
[0012] Furthermore, the copper salt in step (2) is one of copper nitrate, copper sulfate and copper chloride.
[0013] Furthermore, the temperature of the temperature control condition in step (4) is 140-240° C., and the time of the hydrothermal crystallization treatment is 24-120 hours.
[0014] Furthermore, the calcination temperature in step (5) is 350-450° C., and the calcination time is 4-8 hours.
[0015] In a third aspect, the present invention discloses an application of the above-mentioned catalyst for preparing aniline by liquid-phase hydrogenation of nitrobenzene in a reaction of preparing aniline by liquid-phase hydrogenation of nitrobenzene.
[0016] Furthermore, when the catalyst is used in the reaction of nitrobenzene liquid phase hydrogenation to produce aniline, the reaction conditions are: reaction temperature 120-180°C, reaction pressure normal pressure, hydrogen flow rate 250-400ml / min, nitrobenzene liquid hourly space velocity 0.4-1.2h -1 .
[0017] It can be seen from the above technical solutions that the technical solutions of the present invention have the following beneficial effects: The invention provides a catalyst for preparing aniline by liquid-phase hydrogenation of nitrobenzene, and a preparation method and application thereof, which relate to the field of catalysts. During the preparation, a zirconium nitrate solution is reacted with an alkali, and a ZrO2 fine particle precipitate is prepared under the action of ultrasound to form a crystal nucleus for subsequent crystallization. Meanwhile, silica sol, an inorganic aluminum salt, an organic ammonium template and an alkali solution are uniformly mixed, and copper salt is added under the action of ultrasound to form a gel, which is then added to the ZrO2 fine particle precipitate, and a copper-containing skeleton molecular sieve structure is generated on the surface of the ZrO2 fine particle precipitate through a hydrothermal crystallization treatment.
[0018] The technical solution of the present invention not only obtains a suitable pore structure for the catalyst, but also gives full play to the shape-selective effect of the molecular sieve, and also makes the active components dispersed more evenly and firmly, thereby ensuring the activity, selectivity and stability of the catalyst. The advantages include the following: The present invention uses ZrO2 fine particles as crystal nuclei and covers the surface of the particles with a growing molecular sieve to improve the activity of the catalyst carrier, promote the dispersion of active components, and utilize the shape selectivity of the molecular sieve pore size on the catalyst surface to improve the selectivity of aniline. The present invention introduces Cu during the preparation of the molecular sieve to form a Cu-containing skeleton molecular sieve structure, which promotes the dispersion of active components, strengthens the interaction between the active components and the carrier, and inhibits the loss of active components in the liquid phase reaction. The technical method adopted by the present invention is simple, is conducive to industrial application and promotion, and has important social and economic significance; The catalyst prepared by the invention is applied to the reaction of preparing aniline by liquid phase hydrogenation of nitrobenzene, the aniline conversion rate reaches 100%, and the aniline selectivity reaches 99.99%, that is, the prepared catalyst has excellent activity, selectivity and stability.
[0019] It should be appreciated that all combinations of the foregoing concepts, as well as additional concepts described in greater detail below, may be considered to be part of the inventive subject matter of the present disclosure, provided such concepts are not mutually inconsistent. Implementation
[0020] The silicon-based hydrogenation catalyst disclosed in the present invention and its preparation method and application are further specifically introduced below in conjunction with specific embodiments. Example 1
[0021] Step 1) Weigh 152.7 g of zirconium nitrate nonahydrate and 48.8 g of NaOH and dissolve them in 500 ml of deionized water to prepare a zirconium nitrate solution and an alkaline solution. Under the action of ultrasound, add the zirconium nitrate solution to the alkaline solution to obtain a suspension of ultrafine Zr(OH)4 precipitate; Step 2) Weigh 92.2 g of silica sol (40% wt), 4.6 g of aluminum nitrate nonahydrate, 11.4 g of tetrapropylammonium bromide, and 40 g of NaOH, mix them evenly to obtain a molecular sieve precursor, weigh 58.4 g of copper nitrate to prepare a 200 ml solution, add the copper nitrate solution to the molecular sieve precursor under the action of ultrasound, and mix them evenly to obtain a gel; Step 3) adding the obtained gel to the suspension in step 1) and continuing stirring for 20 minutes to obtain a catalyst precursor; Step 4) placing the obtained catalyst support precursor into a reaction kettle and subjecting it to hydrothermal crystallization treatment at 160° C. for 48 hours; Step 5) The product was poured out, washed, filtered, dried, granulated, and calcined at 400° C. for 4 h. Finally, water and a binder were added to extrude the product to obtain catalyst C1. Example 2
[0022] Step 1) Weigh 108.6 g of zirconium nitrate nonahydrate and 34.7 g of NaOH and dissolve them in 500 ml of deionized water to prepare a zirconium nitrate solution and an alkaline solution. Under the action of ultrasound, add the zirconium nitrate solution to the alkaline solution to obtain a suspension of ultrafine Zr(OH)4 precipitate; Step 2) Weigh 206.9 g of silica sol (40% wt), weigh 1.36 g of aluminum hydroxide, 9.66 g of tetrabutylammonium bromide, and 30 g of NaOH, mix them evenly to obtain a molecular sieve precursor, weigh 46.7 g of copper nitrate to make a 200 ml solution, add the copper nitrate solution to the molecular sieve precursor under the action of ultrasound, mix evenly to obtain a gel; Step 3) adding the obtained gel to the suspension in step 1) and continuing stirring for 30 minutes to obtain a catalyst precursor; Step 4) placing the obtained catalyst support precursor into a reaction kettle and subjecting it to hydrothermal crystallization treatment at 180° C. for 72 hours; Step 5) The product is poured out, washed, filtered, dried, granulated, and calcined at 420° C. for 4 h. Finally, water and a binder are added to extrude the product to obtain catalyst C2. Example 3
[0023] Step 1) Weigh 71.3 g of zirconium nitrate nonahydrate and 31.9 g of KOH and dissolve them in 500 ml of deionized water to prepare a zirconium nitrate solution and an alkaline solution. Under the action of ultrasound, add the zirconium nitrate solution to the alkaline solution to obtain a suspension of ultrafine Zr(OH)4 precipitate; Step 2) Weigh 203.7 g of silica sol (40% wt), weigh 2.29 g of aluminum chloride, 11.10 g of tetrabutylammonium bromide, and 50 g of KOH, mix them evenly to obtain a molecular sieve precursor, weigh 58.4 g of copper nitrate to make a 200 ml solution, add the copper nitrate solution to the molecular sieve precursor under the action of ultrasound, mix evenly to obtain a gel; Step 3) adding the obtained gel to the suspension in step 1) and continuing stirring for 40 minutes to obtain a catalyst precursor; Step 4) placing the obtained catalyst support precursor into a reaction kettle and subjecting it to hydrothermal crystallization treatment at 240° C. for 24 hours; Step 5) The product is poured out, washed, filtered, dried, granulated, and calcined at 450° C. for 4 h. Finally, water and a binder are added to extrude the product to obtain catalyst C3. Example 4
[0024] Step 1) Weigh 61.1 g of zirconium nitrate nonahydrate and 27.3 g of KOH and dissolve them in 500 ml of deionized water to prepare a zirconium nitrate solution and an alkaline solution. Under the action of ultrasound, add the zirconium nitrate solution to the alkaline solution to obtain a suspension of ultrafine Zr(OH)4 precipitate; Step 2) Weigh 232.8 g of silica sol (40% wt), weigh 3.36 g of aluminum sulfate, 9.72 g of tetrabutylammonium hydroxide, and 45 g of KOH, mix them evenly to obtain a molecular sieve precursor, weigh 58.4 g of copper nitrate to make a 200 ml solution, add the copper nitrate solution to the molecular sieve precursor under the action of ultrasound, and mix them evenly to obtain a gel; Step 3) adding the obtained gel to the suspension in step 1) and continuing stirring for 25 minutes to obtain a catalyst precursor; Step 4) placing the obtained catalyst support precursor into a reaction kettle and subjecting it to hydrothermal crystallization treatment at 140° C. for 120 h; Step 5) The product is poured out, washed, filtered, dried, granulated, and calcined at 350° C. for 8 h. Finally, water and a binder are added to extrude the product to obtain catalyst C4. Example 5
[0025] Step 1) Weigh 152.7 g of zirconium nitrate nonahydrate and 48.8 g of NaOH and dissolve them in 500 ml of deionized water to prepare a zirconium nitrate solution and an alkaline solution. Under the action of ultrasound, add the zirconium nitrate solution to the alkaline solution to obtain a suspension of ultrafine Zr(OH)4 precipitate; Step 2) Weigh 92.8 g of silica sol (40% wt), weigh 2.9 g of aluminum nitrate nonahydrate, 11.4 g of tetrapropylammonium bromide, and 40 g of NaOH, mix them evenly to obtain a molecular sieve precursor, weigh 58.4 g of copper nitrate to make a 200 ml solution, add the copper nitrate solution to the molecular sieve precursor under the action of ultrasound, and mix them evenly to obtain a gel; Step 3) adding the obtained gel to the suspension in step 1) and continuing stirring for 25 minutes to obtain a catalyst precursor; Step 4) placing the obtained catalyst support precursor into a reaction kettle and subjecting it to hydrothermal crystallization treatment at 200° C. for 60 h; Step 5) The product is poured out, washed, filtered, dried, granulated, and calcined at 380° C. for 74 h. Finally, water and a binder are added to extrude the product to obtain catalyst C5. Example 6
[0026] Step 1) Weigh 152.7 g of zirconium nitrate nonahydrate and 48.8 g of NaOH and dissolve them in 500 ml of deionized water to prepare a zirconium nitrate solution and an alkaline solution. Under the action of ultrasound, add the zirconium nitrate solution to the alkaline solution to obtain a suspension of ultrafine Zr(OH)4 precipitate; Step 2) Weigh 92.2 g of silica sol (40% wt), 4.6 g of aluminum nitrate nonahydrate, 11.4 g of tetrapropylammonium bromide, and 40 g of NaOH, mix them evenly to obtain a molecular sieve precursor, weigh 58.4 g of copper nitrate to prepare a 200 ml solution, add the copper nitrate solution to the molecular sieve precursor under the action of ultrasound, and mix them evenly to obtain a gel; Step 3) adding the obtained gel to the suspension in step 1) and continuing stirring for 40 minutes to obtain a catalyst precursor; Step 4) placing the obtained catalyst support precursor into a reaction kettle and subjecting it to hydrothermal crystallization treatment at 220° C. for 80 h; Step 5) The product is poured out, washed, filtered, dried, granulated, and calcined at 420° C. for 4 h. Finally, water and a binder are added to extrude the product to obtain catalyst C6. Example 7
[0027] Step 1) Weigh 152.7 g of zirconium nitrate nonahydrate and 48.8 g of NaOH and dissolve them in 500 ml of deionized water to prepare a zirconium nitrate solution and an alkaline solution. Under the action of ultrasound, add the zirconium nitrate solution to the alkaline solution to obtain a suspension of ultrafine Zr(OH)4 precipitate; Step 2) Weigh 92.2 g of silica sol (40% wt), 4.6 g of aluminum nitrate nonahydrate, 11.4 g of tetrapropylammonium bromide, and 40 g of NaOH, mix them evenly to obtain a molecular sieve precursor, weigh 58.4 g of copper nitrate to prepare a 200 ml solution, add the copper nitrate solution to the molecular sieve precursor under the action of ultrasound, and mix them evenly to obtain a gel; Step 3) adding the obtained gel to the suspension in step 1) and continuing stirring for 20 minutes to obtain a catalyst precursor; Step 4) placing the obtained catalyst support precursor into a reaction vessel and subjecting it to hydrothermal crystallization treatment at 240° C. for 96 hours; Step 5) The product is poured out, washed, filtered, dried, granulated, and calcined at 400° C. for 8 h. Finally, water and a binder are added to extrude the product to obtain catalyst C7. Example 8
[0028] The catalyst was applied to the liquid phase hydrogenation of nitrobenzene to produce aniline.
[0029] Take C1-C7 catalyst, crush it into 20-40 mesh, take 10ml catalyst, load it into fixed bed reactor, reduce the catalyst at 180℃, 0.2MPa, 5% hydrogen concentration nitrogen and hydrogen atmosphere for 12h before reaction, cool to 160℃, reaction pressure normal pressure, nitrobenzene feed amount 0.6h -1 , H2 flow rate 250ml / min, the results are shown in Table 1.
[0030] Table 1 Activity evaluation results
[0031] It can be seen from the data in Table 1 that when the catalyst designed by the technical solution of the present invention is applied to the liquid phase hydrogenation of nitrobenzene to produce aniline, the conversion rate of nitrobenzene reaches 100%, the selectivity of aniline reaches more than 99%, and the catalyst performance is good. Example 9
[0032] Take 10 ml of C1 catalyst and load it into a fixed bed reactor. Before the reaction, reduce the catalyst at 180°C, 0.2 MPa, and 5% hydrogen concentration in nitrogen and hydrogen atmosphere for 12 hours, cool it to 120°C, and set the reaction pressure to normal pressure. Feed nitrobenzene for 0.8 h -1 , H2 flow rate 400ml / min, the results are shown in Table 2. Example 10
[0033] Take 50ml of C1 catalyst and load it into a fixed bed reactor. Before the reaction, reduce the catalyst at 180℃, 0.2MPa, and 5% hydrogen concentration nitrogen and hydrogen atmosphere for 12h, cool it to 140℃, and react at normal pressure. Nitrobenzene feed rate is 1.2h. -1 , H2 flow rate 300ml / min, the results are shown in Table 2. Embodiment 11
[0034] Take 50 ml of C1 catalyst and load it into a fixed bed reactor. Before the reaction, reduce the catalyst at 180°C, 0.2 MPa, and 5% hydrogen concentration in nitrogen and hydrogen atmosphere for 12 hours. Maintain 180°C, reaction pressure normal pressure, and nitrobenzene feed rate 0.4h -1 , H2 flow rate 250ml / min, the results are shown in Table 2.
[0035] Table 2 Effect of reaction conditions on activity evaluation results
[0036] From Table 2, we can see that at a reaction temperature of 140°C-180°C and a reaction pressure of normal pressure, the nitrobenzene feed rate is 0.4-1.2h -1 The catalysts all showed excellent catalytic effects, had excellent stability, were suitable for industrial reaction conditions, and were conducive to industrial promotion.
Claims
1. A catalyst for preparing aniline by liquid phase hydrogenation of nitrobenzene, characterized in that: The catalyst has a core-shell structure of ZrO2@Cu-containing skeleton molecular sieve, wherein the molecular sieve structure is a modified molecular sieve doped with active component Cu, and the carrier content is 70-80% by mass, the ZrO2 / molecular sieve mass ratio is 1:1-1:4, and the active component CuO content is 20-30%.
2. The catalyst for preparing aniline by liquid phase hydrogenation of nitrobenzene as claimed in claim 1, characterized in that: The specific surface area of the catalyst is 180-350 2 / g, average pore diameter 15-35nm, pore volume 0.21-0.45cm 3 / g.
3. The method for preparing a catalyst for preparing aniline by liquid phase hydrogenation of nitrobenzene as claimed in claim 1 or 2, characterized in that: The steps include: 1) adding zirconium salt into alkaline solution under the action of ultrasound to prepare a suspension of ultrafine nanocrystalline cores; 2) After uniformly mixing silica sol, inorganic aluminum salt, alkaline solution and organic ammonium template, Cu salt is added under ultrasonic action to obtain gel; wherein the inorganic aluminum salt is one of aluminum sulfate, aluminum nitrate, aluminum chloride and aluminum hydroxide; 3) adding the gel in step 2) to the suspension in step 1) and continuing stirring for 20-40 minutes to obtain a catalyst precursor solution; 4) Under temperature control conditions, the catalyst precursor solution is subjected to hydrothermal crystallization treatment in a reactor; 5) The product of the hydrothermal crystallization treatment is washed, filtered, dried, granulated, calcined and formed to obtain a core-shell structure ZrO2@Cu-containing skeleton molecular sieve catalyst.
4. The method for preparing a catalyst for preparing aniline by liquid phase hydrogenation of nitrobenzene as claimed in claim 3, characterized in that: The alkali in the alkali solution in steps 1) and 2) is NaOH or KOH.
5. The method for preparing a catalyst for preparing aniline by liquid phase hydrogenation of nitrobenzene as claimed in claim 3, characterized in that: The organic ammonium template in step 2) is tetrabutylammonium bromide, tetrapropylammonium bromide, tetrabutylammonium hydroxide or tetrapropylammonium hydroxide.
6. The method for preparing a catalyst for preparing aniline by liquid phase hydrogenation of nitrobenzene as claimed in claim 3, characterized in that: The copper salt in step (2) is one of copper nitrate, copper sulfate and copper chloride.
7. The method for preparing a catalyst for preparing aniline by liquid phase hydrogenation of nitrobenzene as claimed in claim 3, characterized in that: The temperature of the temperature control condition in the step (4) is 140-240° C., and the time of the hydrothermal crystallization treatment is 24-120 hours.
8. The method for preparing a catalyst for preparing aniline by liquid phase hydrogenation of nitrobenzene as claimed in claim 3, characterized in that: The calcination temperature in step (5) is 350-450° C. and the calcination time is 4-8 hours.
9. Use of the catalyst for preparing aniline by liquid-phase hydrogenation of nitrobenzene as claimed in claim 1 or 2 in the reaction of preparing aniline by liquid-phase hydrogenation of nitrobenzene.
10. The use of the catalyst for preparing aniline by liquid phase hydrogenation of nitrobenzene as claimed in claim 9, characterized in that: When the catalyst is used in the reaction of preparing aniline by hydrogenation of nitrobenzene in liquid phase, the reaction conditions are: reaction temperature 120-180°C, reaction pressure normal pressure, hydrogen flow rate 250-400 ml / min, nitrobenzene liquid hourly space velocity 0.4-1.2 h -1 .
Citation Information
Patent Citations
Catalyst used in nitrobenzene liquid-phase hydrogenation aniline synthesis, and preparation method thereof
CN103316676A
Multifunctional catalyst having nano / micro-scale reaction and separation coupling function and preparation method thereof
CN104258896A
Method for preparing aniline through nitrobenzene hydrogenation and preparation method for catalyst used in method
CN111085241A
Catalyst for preparing aniline through nitrobenzene hydrogenation as well as preparation method and application of catalyst
CN114588941A
Catalyst for preparing aniline through nitrobenzene hydrogenation as well as preparation method and application of catalyst
CN115999548A